Intelligent M.V. circuit-breakers: recent evolutions - Morant, M; Bonjean, M; Thiry, P; Wysota, D (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
With the recent evolution of circuit breaking chambers, high current interruption is no longer a problem. The more profitable benefits, both on the technological and the economical points of view, lead to an increase of the added value of a circuit-breaker in the power network. Soon it will also be possible to integrate the circuit-breaker in the managing process of a substation, by using a digital linkage to the drive. By introducing a new drive principle, based on an asymmetrical magnetic actuator, the operating mechanism can be very simple and will integrate directly this communication philosophy. It is assumed that the standards will rapidly define the communication protocols between devices. This is already the subject of an IEC working group. (5 pages)